2007
DOI: 10.1073/pnas.0611217104
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic profiling of phosphopeptides using electron transfer dissociation tandem mass spectrometry

Abstract: Electron transfer dissociation (ETD) is a recently introduced massspectrometric technique that provides a more comprehensive coverage of peptide sequences and posttranslational modifications. Here, we evaluated the use of ETD for a global phosphoproteome analysis. In all, we identified a total of 1,435 phosphorylation sites from human embryonic kidney 293T cells, of which 1,141 (Ϸ80%) were not previously described. A detailed comparison of ETD and collision-induced dissociation (CID) modes showed that ETD iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
490
2
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 481 publications
(514 citation statements)
references
References 22 publications
20
490
2
2
Order By: Relevance
“…A parameter file incorporating the following mass modifications was used in the search for glycated peptides: static modification for cysteine residues (carbamidomethylation, 57.02 Da), dynamic modification for methionine residues (oxidation, 16.00 Da), and dynamic modification for lysine residues (AC, 162.05 Da). Additionally, the following charge-dependent criteria that were modified from Molina et al 22 were used to filter raw search results: 5+, score >14; 4+, score >12; 3+, score >9; 2+, score >8; a percentage scored peak intensity (%SPI) >60 and Delta Rank1 − Rank2 >1 were used for all charge states. Further, each data set was searched against the same IPI database with all protein sequences reversed in order to estimate the peptide false discovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…A parameter file incorporating the following mass modifications was used in the search for glycated peptides: static modification for cysteine residues (carbamidomethylation, 57.02 Da), dynamic modification for methionine residues (oxidation, 16.00 Da), and dynamic modification for lysine residues (AC, 162.05 Da). Additionally, the following charge-dependent criteria that were modified from Molina et al 22 were used to filter raw search results: 5+, score >14; 4+, score >12; 3+, score >9; 2+, score >8; a percentage scored peak intensity (%SPI) >60 and Delta Rank1 − Rank2 >1 were used for all charge states. Further, each data set was searched against the same IPI database with all protein sequences reversed in order to estimate the peptide false discovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…Molina et al also compared the use of ETD and CID for fragmentation, and identified 60% more phosphopeptides when using ETD, mainly due to an average of 40% more fragment ions. However, the authors found that a combination of ETD and CID by an automatic alternating mode gave the best results as little overlap was observed from the two fragmentation techniques [85].…”
Section: Electron Transfer Dissociationmentioning
confidence: 99%
“…Furthermore, TiO 2 is extremely tolerant toward most buffers and salts used in biochemistry and cell biology laboratories [73]. This has resulted in a robust method for enrichment of phosphopeptides, which has already become a highly popular method for in large-scale phosphoproteomic studies [10,[77][78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: Titanium Dioxide Chromatographymentioning
confidence: 99%
See 2 more Smart Citations